The impact of promotional activities to customer's purchasing behaviour for Pemasaran Melaka Sdn. Bhd. / Ridzwan Hafidz Rosli - Rosli, Ridzwan Hafidz (2014)
Pemasaran Melaka Sdn Bhd is a company that market Melaka products. During the first few years of its establishment, the customer accepted Pemasaran Melaka positively by the local authority. However, in the recent years, the acceptances of Pemasaran Melaka were slightly reduced. According to managing director of PMSB, this could due to low of promotional activities conducted by PMSB compared to when it was first established. Thus, this research is to study on how promotional activities conducted by PMSB will influence the purchasing behavior of its customer. The objective of this study is to determined level purchasing behavior of customer at PMSB, to determine the relationship between promotional activities and purchasing behavior at PMSB, to investigate which promotional is most influence purchasing behavior at PMSB and to give the recommendation to the company on promotional tools they can use in time to come. As for the research methodology, or the research design, descriptive, exploratory and conclusive research will be used. For the sampling technique, convenience sampling (non-probability sampling) will be used where the researcher will distribute 80 questionnaires to customer of PMSB. Reliability test, frequency, descriptive, correlation and regression has been used in this study to get the data from the questionnaire. Lastly, for the findings, the result shows Personal Selling is the most effective tool while Public Relation is the least effective tool. The research also provides some recommendation to PMSB to improve their promotion efforts to become more effective. All the data gathered from the questionnaire will be analyzed using Statistic Package for Social Science (SPSS) version 20.0.